The Changing Style and Meaning of Damono’s Translated Poems - Lilis Lestari Wilujeng; G.A.D. Shanty Arysaputri (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2018)
Translating poems is different from translating other kinds of documents such as scientific articles, textbooks, and the like, since the translator is expected not only to transfer the meaning, but also the original poems’ style and other important aspects. Related to it, the objective of this analysis is to identify the changing style and meaning of Sapardi Djoko Damono’s poems translated and compiled in an anthology entitled Before Dawn by John H. McGlynn. In this research, descriptive qualitative method and stylistic approach were utilized in analyzing the data, interpreting the resulting findings, and reporting the analysis. The focus of analysis is on the four compared literary devices of Indonesian and English versions of the selected poems, i.e. theme, imagery, diction, tone and mood. The results of analysis show that several changes on those four aspects were identified in the selected poems of the anthology. The changes mostly happen in their theme, tone, and mood. The poems’ style also slightly changed after being translated into English. They had simpler and more concise style of description, yet elegant and beautiful in structure and diction. Thus, the translation of those poems is proven to have several changes in terms of style and other literary devices so as to influence the poems’ meanings.